2022
DOI: 10.1177/07916035221088408
|View full text |Cite
|
Sign up to set email alerts
|

Walking and talking with girls in their urban environments: A methodological meandering

Abstract: Young people spend a lot of time in their neighbourhood, yet little is known about the relationship between wellbeing, belonging and place from their own perspective. Our study sought to understand how young people navigate their neighbourhood and perceive various aspects of its health environment in its broadest sense. In this article we reflect on the walking methodology we used as part of a Participatory Photo Mapping (PPM) exercise with 11-year-old girls from a working-class school community who were parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This mobile method allowed reflections on the everyday food practices of participants as they unfolded in time and space (Carpiano, 2009;Kusenbach, 2003). Previous studies have found that participatory approaches with children and young people, such as go-along interviews, have the potential to reduce the power imbalance between researcher and participants by situating the young person as the expert guide (Hayball & Pawlowski, 2018;Horgan et al, 2022).…”
Section: Data Collectionmentioning
confidence: 99%
“…This mobile method allowed reflections on the everyday food practices of participants as they unfolded in time and space (Carpiano, 2009;Kusenbach, 2003). Previous studies have found that participatory approaches with children and young people, such as go-along interviews, have the potential to reduce the power imbalance between researcher and participants by situating the young person as the expert guide (Hayball & Pawlowski, 2018;Horgan et al, 2022).…”
Section: Data Collectionmentioning
confidence: 99%